Conductive conductor

By forming a high adhesion metal layer on the surface of aluminum or aluminum alloy conductors, the problems of increased contact resistance and reduced conductivity caused by oxidation of conductive wires are solved, and the high corrosion resistance and conductivity of conductive wires are achieved, and the manufacturing process is simplified.

JP2025039529APending Publication Date: 2025-03-21DAIDEN CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024140107
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-08
Filing Date
2024-08-21
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, aluminum alloy conductive wires tend to increase contact resistance and reduce solderability due to oxidation, and traditional plating treatment methods are complex and costly, and plating of low-conductive elements such as silicon or boron will reduce electrical conductivity.

Method used

Aluminum or aluminum alloy is used as the conductor material, and the corrosion resistance and conductivity of the conductive wires are improved by tin plating or other metal layers. By forming a metal carbide or other metal layer with high adhesion on the surface of the aluminum conductor, oxidation is prevented and conductivity is improved.

Benefits of technology

It effectively prevents oxidation of the surface of aluminum conductors, improves the corrosion resistance and conductivity of conductive wires, reduces contact resistance, simplifies the manufacturing process, and improves working efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039529000001_ABST
    Figure 2025039529000001_ABST
Patent Text Reader

Abstract

To provide a conductive conductor that achieves improved durability by suppressing formation of impurities, including oxide films, formed on the surface of the conductor.SOLUTION: A conductive conductor includes: a conductor formed from one metal element or an alloy thereof; and a coating layer, formed from another metal element different from the one metal element or from a carbide thereof, which covers the conductor and has an uneven shape on its surface on the inner side.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive conductor used for electrical conduction, and more particularly to a conductive conductor having improved durability. [Background technology]

[0002] Conductive conductors play an important role in various cable applications such as signal transmission and power supply, and in recent years, the need for them has been increasing in a wide range of fields.

[0003] Conventional conductors have mainly been made of copper due to its advantages such as high conductivity. However, in recent years, aluminum, which can be made significantly lighter than copper and has a relatively high conductivity, has been attracting attention as a conductor material to replace copper in the future.

[0004] In particular, aluminum alloys such as aluminum-iron (Al-Fe) have the advantages of being lightweight (one-third the weight of copper), highly durable, capable of being made into thin wires, and having higher tensile strength than conventional aluminum wires.

[0005] However, aluminum is one of the metals that is particularly susceptible to oxidation. In particular, the formation of a strong oxide film (aluminum oxide) on the metal surface reduces the reliability of the electrical connection with the terminals, increases contact resistance, and reduces solderability.

[0006] For example, in recent years, the need for weight reduction has led to the replacement of copper wire with aluminum wire as the conductor for electrical wiring cables used inside mechanical equipment such as automobiles, and in FA equipment and robots. Electrical wiring cables for such applications require surface treatment to apply tin (Sn) plating to the outermost surface to improve solder connectivity, and an intermediate layer is required to ensure adhesion between the above-mentioned aluminum alloy, which forms the cable conductor, and the tin plating, but oxides on the aluminum surface reduce the adhesion of the tin plating.

[0007] In order to solve this problem particular to aluminum metal, that of being easily oxidized, various conductive conductors have been proposed in which the oxide film on the surface of the aluminum conductor is first removed and then plated with a metal other than aluminum using a wet plating method or an electroplating method (hereinafter, plating method also refers to such ordinary plating methods using wet plating method or electroplating method).

[0008] For example, a method for applying a highly adhesive metal plating treatment to the surface of an aluminum conductor as a conductive conductor is known in which the aluminum conductor is pickled to remove the oxide film on the conductor surface, and then zincate treated once or twice or more times to form a zinc underlayer (zinc-containing layer), and then a desired plating treatment is applied using a wet plating method or an electroplating method.

[0009] However, plating processes, like the zincate process, have many problems, such as complicated pretreatment and high costs.

[0010] For this reason, plating treatments that do not use zincate treatment are also being considered. For example, a plating treatment has been disclosed in which an activation treatment of the aluminum surface is performed in a wet plating method to intentionally form an oxide layer consisting of an aluminum component, a plating metal component, and an oxygen component in the boundary region between the aluminum surface and the plating film, thereby improving the adhesion between metals in the plating treatment.

[0011] As such a conventional conductive conductor, for example, a plated wire rod having a base material made of aluminum and a surface treatment coating composed of one or more metal layers and covering the base material, in which the lowermost metal layer, which is a metal layer formed on the base material among the one or more metal layers, is nickel, a nickel alloy, cobalt, or a cobalt alloy, and a mixed layer containing metal components in the base material, metal components in the surface treatment coating, and an oxygen component is present at the interface between the base material and the surface treatment coating (see Patent Document 1).

[0012] Also, for example, a conventional conductive conductor is a plated wire rod having a wire rod made of aluminum and a surface treatment coating composed of one or more metal layers and covering the wire rod, wherein the boundary region between the wire rod and the surface treatment coating has a mixed layer containing the metal components in the wire rod and the metal components and oxygen components in the surface treatment coating, and among the one or more metal layers constituting the surface treatment coating, a lowermost metal layer which is the metal layer located closest to the wire rod is a layer of copper or a copper alloy (see Patent Document 2).

[0013] However, even with these improved plating processes, an oxide film can form on the conductor aluminum, resulting in plating with poor adhesion. In addition, the need for pretreatment makes the process complicated and increases the cost of the process. Another problem is that the coating is prone to peeling off due to the formation of voids on the order of μm caused by the surface tension that inevitably occurs at the interface of the plating solution.

[0014] In view of this, sputtering has been investigated as a method for forming a metal coating with high adhesion without the need for the pretreatment required for such plating.

[0015] For example, a conventional conductive conductor using a sputtering method is a manufacturing method for a copper conductor, which has a different main metal from that of an aluminum conductor, and includes a conductive conductor made by bundling a plurality of copper wires into a twisted wire, in which a Si coating layer is formed on the surface of at least the copper wires located in the outer layer, and the Si coating layer is formed by a sputtering method (see Patent Document 3).

[0016] Also, for example, in a conductor for a coated electric wire in which a plurality of copper wires are bundled together to form a stranded wire, at least the copper wires located in the outer layer have a coating layer B formed on the surface thereof, and the coating layer B is formed by a sputtering method (see Patent Document 4). .

[0017] Also, although it is a manufacturing method for a superconducting wire different from a conductive conductor, for example, a manufacturing method for a superconducting wire is known, which includes a step of forming a metal film containing at least one of Nb, Ti, Ta, W, Mo, and Fe on the metal base material, a thin film formation step of forming the MgB2 thin film or a mixture thin film of Mg and B on the metal film, a protective layer formation step of forming a protective layer on the thin film formed by the thin film formation step, and a heat treatment step of performing a heat treatment at a temperature equal to or higher than the film formation temperature of the MgB2 thin film after the protective layer formation step, in which the thin film formation step forms the thin film by sputtering a B or a mixture target of Mg and B and vapor deposition of Mg (see Patent Document 5).

[0018] Similarly, although it is a manufacturing method for superconducting wire that is different from a conductive conductor, for example, a manufacturing method for superconducting thin film wire in which a thin film is manufactured from a first substance and a second substance having a higher melting point or vapor pressure than the first substance is known, the manufacturing method for superconducting thin film wire having a first step of forming a reaction prevention film on a metal substrate, a second step of heating and evaporating the first substance or sputtering the second substance in a direction parallel to the metal substrate surface, and a third step of sputtering the second substance, or the first substance and the second substance (see Patent Document 6). [Prior art documents] [Patent documents]

[0019] [Patent Document 1] International Publication No. 2018 / 181399 [Patent Document 2] International Publication No. 2019 / 193960 [Patent Document 3] Japanese Patent Application Publication No. 2-162611 [Patent Document 4] Japanese Patent Application Publication No. 2-162608 [Patent Document 5] JP 2020-61235 A [Patent Document 6] JP 2019-183226 A Summary of the Invention [Problem to be solved by the invention]

[0020] However, as a method for solving the problems of the plating process, there is a manufacturing method in which sputtering is performed on a copper conductor as in the above Patent Documents 3 and 4, but the electrical conductivity of the cable decreases when a coating using an element with low electrical conductivity, such as a Si coating layer or a B coating layer, is used. Also, since copper and aluminum conductors differ greatly in properties such as hardness, electrical conductivity, and weight, the manufacturing methods in which sputtering is performed as in the above Patent Documents 3 and 4, which are intended for copper conductors, cannot be directly applied to those using aluminum conductors as strands.

[0021] In addition, there are manufacturing methods in which sputtering is performed on superconducting wire, as described in Patent Documents 5 and 6 above. However, the principles of electrical conduction for superconducting wire and for electrical conductors are fundamentally different technologies, and the manufacturing methods described in Patent Documents 5 and 6 above cannot be directly applied to wires made of aluminum conductors.

[0022] The present invention has been made to solve the above-mentioned problems, and aims to provide a conductive conductor that suppresses the formation of impurities such as oxide films on the surface of the conductive conductor and improves durability. [Means for solving the problem]

[0023] As a result of extensive research, the present inventors discovered a conductor for electrical conduction having improved durability through the use of an improved conductive coating, and completed the conductor for electrical conduction according to the present invention.

[0024] Thus, the conductor for electrical conduction disclosed in the present application is composed of a conductor made of one metal element or its alloy, and a coating layer made of another metal element different from the one metal element or its carbide, covering the conductor, and having an uneven shape on the surface on the inner side surface. Since the conductor for electrical conduction disclosed in the present application is composed of a conductor made of one metal element or its alloy, and a coating layer made of another metal element different from the one metal element or its carbide, covering the conductor, and having an uneven shape on the surface on the inner side surface, the uneven shape provides high adhesion between the conductor and the coating layer, making it difficult for impurities such as an oxide film to form on the conductor surface, and suppressing the contact resistance generated in the conductor.

[0025] In the conductive conductor disclosed in the present application, the one metal element is aluminum, and the other metal element is at least one of gold, silver, copper, nickel, tin, titanium, platinum, silicon, cobalt, ruthenium, rhodium, palladium, and indium, as necessary. Since the one metal element is aluminum and the other metal element is at least one of gold, silver, copper, nickel, tin, titanium, platinum, silicon, cobalt, ruthenium, rhodium, palladium, and indium, the uneven shape provides high adhesion between the conductor and the coating layer, making it difficult for an aluminum oxide film to form on the conductor surface, and suppressing the contact resistance generated in the conductor.

[0026] In the conductor for electrical conduction disclosed in the present application, the other metal element is at least one of gold, silver, copper, nickel, and tin, as necessary. Since the other metal element is at least one of gold, silver, copper, nickel, and tin, the other metal element capable of firmly coating the conductor and the uneven shape act synergistically to obtain high adhesion between the conductor and the coating layer, making it difficult for an aluminum oxide film to form on the conductor surface, and the conductor Therefore, the contact resistance occurring in the contact hole can be suppressed.

[0027] In addition, in the conductor for electrical conduction disclosed in the present application, the uneven shape of the coating layer is formed in an anchoring manner as necessary. Since the uneven shape of the coating layer is formed in an anchoring manner, the coating layer penetrates into minute gaps present on the surface of the conductor and acts like a wedge, and the uneven shape formed in an anchoring manner provides high adhesion between the conductor and the coating layer, making it difficult for impurities such as an oxide film to form on the conductor surface, and suppressing the contact resistance occurring in the conductor.

[0028] In addition, the conductive conductor disclosed in the present application is formed, as necessary, by fitting the conductor surface with the uneven shape of the coating layer by sputtering. Since the uneven shape of the coating layer is formed by fitting the conductor surface with sputtering, the coating layer is formed without containing a zinc intermediate layer as in the case of using the plating process of the conventional technology, and in addition to improving the quality of the conductor with a simple configuration, the complicated pretreatment as in the case of using the plating process of the conventional technology is not required, and the work efficiency can be improved.

[0029] In addition, the conductive conductor disclosed in the present application is one in which the coating layer is continuously formed on the surface of the conductor as necessary. Since the coating layer is continuously formed on the surface of the conductor in this manner, the coating layer is fixed to the surface of the conductor with high adhesion, which makes it difficult for impurities such as an oxide film to form on the conductor surface, and thus makes it possible to suppress the contact resistance generated in the conductor.

[0030] Furthermore, the conductor for electrical conduction disclosed in the present application may, as necessary, have a thickness of the coating layer in the diameter direction of the conductor for electrical conduction that is a film thickness ratio of 0.1% to 5% of the diameter of the conductor for electrical conduction. Since the thickness of the coating layer in the diameter direction of the conductor for electrical conduction is a film thickness ratio of 0.1% to 5% of the diameter of the conductor for electrical conduction, the thickness of the coating layer specified by the film thickness ratio can provide more optimal adhesion between the conductor and the coating layer, making it difficult for impurities such as an oxide film to form on the surface of the conductor, and suppressing the contact resistance occurring in the conductor.

[0031] In addition, the conductor for electrical conduction disclosed in the present application has a thickness of the coating layer of 0.1 μm or more and 10 μm or less, as necessary. Since the thickness of the coating layer is 0.1 μm or more and 10 μm or less, the specified thickness of the coating layer provides more optimal adhesion between the conductor and the coating layer, making it difficult for impurities such as an oxide film to form on the conductor surface, and suppressing the contact resistance generated in the conductor.

[0032] Furthermore, in the conductor for electrical conduction disclosed in the present application, the adhesive strength of the coating layer to the conductor is 6 N or more, as necessary. Since the adhesive strength of the coating layer to the conductor is 6 N or more, an optimal degree of adhesiveness can be obtained between the conductor and the coating layer due to the adhesive strength of the coating layer to the conductor, impurities such as an oxide film are less likely to form on the surface of the conductor, and the contact resistance generated in the conductor can be suppressed.

[0033] The manufacturing device for the conductive conductor disclosed in the present application further comprises a coating forming means for forming the coating layer continuously around the entire circumference of the conductor by sputtering. Since the device comprises the coating forming means for forming the coating layer continuously around the entire circumference of the conductor by sputtering, the coating layer is uniformly and evenly coated on the conductor, making it difficult for impurities such as an oxide film to form on the conductor surface covered with the coating layer, suppressing contact resistance occurring in the conductor and significantly improving the durability of the conductive conductor. [Brief description of the drawings]

[0034] [Figure 1] 1 is a configuration diagram of a conductive conductor according to a first embodiment of the present invention; [Diagram 2] FIG. 1 is an explanatory diagram of a sputtering apparatus for manufacturing a conductor for electrical conduction according to a first embodiment of the present invention. [Diagram 3] FIG. 2 is an explanatory diagram for explaining an image of adsorption of deposited particles by sputtering of a conductor for electrical conduction according to the first embodiment of the present invention. [Figure 4] FIG. 1 is a configuration diagram of a manufacturing apparatus (continuous film-forming apparatus) for manufacturing a conductor according to a first embodiment of the present invention. [Diagram 5] 1 shows a surface SEM image of a copper coating formed on an aluminum plate according to Example 1 of the present invention. [Figure 6] 1 shows a surface SEM image of a copper coating formed on an aluminum-iron alloy wire according to Example 1 of the present invention. [Figure 7] 1 shows a cross-sectional SEM image of a copper coating formed on an aluminum-iron alloy wire according to Example 1 of the present invention. [Figure 8] 1 shows a cross-sectional SEM image of a copper coating formed on an aluminum-iron alloy wire according to Example 1 of the present invention. [Figure 9] 1 shows a cross-sectional SEM image of an aluminum-iron alloy wire according to Example 1 of the present invention, in which electrolytic tin plating is applied to a copper coating of the wire. [Figure 10] 1 shows elemental mapping (EDS) of an aluminum-iron alloy wire according to Example 1 of the present invention. [Figure 11] 1 shows an image of a surface roughness measurement sample of an aluminum-iron alloy material having a copper coating formed by sputtering on an aluminum plate according to Example 2 of the present invention. [Figure 12] 1 shows an image of the surface shape of a sample for measuring the surface roughness of an aluminum-iron alloy wire formed by sputtering a copper coating on an aluminum flat plate according to Example 2 of the present invention. [Figure 13] 1 shows the results of a tensile test of an aluminum-iron alloy wire having a copper coating formed by sputtering on an aluminum plate according to Example 3 of the present invention. [Figure 14] 13 shows an SEM image of a sample measurement position for the adhesion of an aluminum-iron alloy wire coated with copper by sputtering on an aluminum flat plate according to Example 4 of the present invention. [Figure 15] 13 shows images of an aluminum-iron alloy wire produced by a sputtering apparatus (continuous film-forming apparatus) according to Example 5 of the present invention, before and after copper sputtering. [Figure 16]FIG. 1 shows a cross-sectional SEM image (upper part) of an Al-Fe wire coated with Cu by a sputtering apparatus (continuous film forming apparatus) according to Example 5 of the present invention, and cross-sectional SEM images (lower part) of each of the (A) upper part, (B) left part, (C) lower part, and (D) right part of the cross-sectional SEM image at 10,000 times magnification. [Figure 17] Among cross-sectional SEM images of an Al-Fe wire coated with Cu by the sputtering apparatus (continuous film-forming apparatus) according to Example 5 of the present invention, cross-sectional SEM images of each of the above-mentioned portions (A) to (D) are shown at 20,000 magnifications. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] (First embodiment) As shown in FIG. 1, the conductor according to the first embodiment is composed of a conductor 1 made of a metal element or its alloy, and a coating layer 2 made of a metal element different from the metal element or its carbide, which coats the conductor 1 and has an uneven shape 21 on the surface on the inner side. .

[0036] The metal element constituting the conductor 1 is not particularly limited, but is preferably aluminum, which is lightweight, and more preferably an aluminum alloy.

[0037] The aluminum alloy is not particularly limited as long as it is an alloy mainly composed of aluminum, and can be, for example, an alloy of aluminum and iron, copper, manganese, silicon, magnesium, zinc, nickel, etc., and among these, for example, an aluminum-iron (Al-Fe) alloy can be used.

[0038] The other metal elements constituting this coating layer 2 are not particularly limited, but are preferably at least one of gold, silver, copper, nickel, tin, titanium, platinum, silicon, cobalt, ruthenium, rhodium, palladium, and indium, and more preferably at least one of gold, silver, copper, nickel, and tin. This uneven shape 21 provides high adhesion between the conductor 1 and the coating layer 2, and this adhesion makes it difficult for impurities such as an aluminum oxide coating to form on the surface of the conductor 1, thereby suppressing the contact resistance generated in the conductor 1.

[0039] The coating layer 2 has an uneven shape 21 on the surface on the inner side. The uneven shape 21 is a shape having projections and recesses that are not smooth in part or in whole, and may be a homogeneous uneven shape 21 or an uneven uneven shape 21. Although there are no particular limitations, it is preferable that the uneven shape is formed in an anchoring manner as shown in Fig. 1.

[0040] The term "anchoringly formed" refers to a state in which the coating layer 2 penetrates into the voids on the surface of the conductor 1 via the unevenness 21 and is hardened to form the coating layer.

[0041] In this way, since the uneven shape 21 of the coating layer 2 is formed in an anchoring manner, the coating layer 2 penetrates into the minute gaps present on the surface of the conductor 1 and acts like a wedge. The uneven shape 21 formed in an anchoring manner provides high adhesion between the conductor 1 and the coating layer 2, making it difficult for impurities such as an oxide film to form on the surface of the conductor 1, and suppressing the contact resistance generated in the conductor 1.

[0042] The uneven shape 21 of the coating layer 2 formed in such an anchoring manner is not particularly limited, but is preferably formed by fitting the surface of the conductor 1 by sputtering. For example, it has been confirmed that a strong Cu sputtered coating is formed by fitting Cu into the uneven shape of the surface of the Al-Fe wire (see the examples described later).

[0043] Sputtering is a process of physical vapor deposition, and an example of a sputtering apparatus, as shown in Fig. 2, can be configured to include a vacuum chamber 200, an inlet 201 for introducing an inert gas such as argon gas, a conductor 1 made of one metal element, and a coating layer metal plate 20 made of another metal element as a target, and an input power 100 as DC power applied between these metal elements. The input power 100 can be in the range of, for example, 200 to 600 W, and the distance between the coating layer 2 metal and the conductor 1 in the vacuum chamber can be set to 100 W. The distance d can be set to, for example, 20 to 80 mm.

[0044] An image of the adsorption of deposition particles made of other metals by sputtering is as shown in Figure 3, in which an inert gas such as argon is introduced into a vacuum, and a negative voltage is applied to the coating layer metal plate 20 (e.g., made of copper metal) to be sputtered to generate a glow discharge and ionize the inert gas atoms, and the inert gas ion particles 300 that have been highly energized in the vacuum are collided with the surface of the coating layer metal plate 20, ejecting metal particles 20a (e.g., copper ions) that make up the coating layer metal plate 20, and the ejected metal particles 20a are deposited on the surface of the conductor 1 (e.g., aluminum-iron alloy wire) to form a coating.

[0045] The advantage of using this sputtering method is that the metal particles that make up the coating layer metal plate 20, which is the target of sputtering, are ionized with high efficiency, so that the coating layer 2 as a film is formed by embedding the surface of the conductor 1 with high adhesion.

[0046] Furthermore, when aluminum or an aluminum alloy is used for the conductor 1, the uneven shape 21 is significantly more easily formed by sputtering since aluminum or an aluminum alloy has high workability, and is therefore highly compatible with sputtering.

[0047] Furthermore, when aluminum is used for the conductor 1 and the coating layer 2 is at least one of, but not limited to, gold, silver, copper, nickel, tin, titanium, platinum, silicon, cobalt, ruthenium, rhodium, palladium, and indium, the excellent conductivity of the coating layer 2 results in a significant skin effect, particularly for high-frequency currents, and a high-density current can be passed through the same diameter, resulting in the advantage of being able to handle larger currents.

[0048] In this way, the uneven shape 21 of the coating layer 2 is formed by fitting the surface of the conductor 1 by sputtering, and therefore is formed without containing a zinc intermediate layer as occurs when the plating process of the conventional technology is used. In addition to improving the quality of the conductor 1 due to the simple configuration, it is possible to eliminate the need for complicated pre-processing as in the plating process of the conventional technology, thereby improving work efficiency.

[0049] In addition, because the uneven shape 21 of the coating layer 2 is formed by fitting the surface of the conductor 1 by sputtering, there is an advantage that there is no room for the formation of voids on the order of μm caused by surface tension that inevitably occurs at the interface of the plating solution surface, as in the case of using the plating process of the conventional technology. In the plating process of the conventional technology, there was a problem that the formation of these voids made the coating prone to peeling, but the coating layer 2 that is denser and more adhesive than the plating process of the conventional technology is formed on the surface of the conductor 1, and the creepage distance can be secured at a minimum distance from the conductor 1, realizing a large current.

[0050] In this way, the conductive conductor of this embodiment has a high adhesion between the conductor 1 and the coating layer 2 due to the uneven shape 21, making it difficult for impurities such as an oxide coating to form on the surface of the conductor 1, and suppressing the contact resistance generated in the conductor 1.

[0051] The roughness of the uneven surface of the uneven shape 21 of the coating layer 2 can be approximated to the roughness of the uneven surface of the outer surface of the coating layer 2, and is not particularly limited, but is preferably such that the arithmetic mean roughness Ra in the longitudinal direction is 0.3 to 0.6 μm, more preferably 0.3 to 0.4 μm. It shows a large uneven shape compared to conventional plating coatings. As a result, the uneven shape 21 specified by the arithmetic mean roughness Ra provides high adhesion between the conductor 1 and the coating layer 2, making it difficult for impurities such as an oxide film to form on the surface of the conductor 1, and suppressing the contact resistance generated in the conductor 1.

[0052] It is also preferable that the coating layer 2 is continuously formed on the surface of the conductor 1. Since the coating layer 2 is continuously formed on the surface of the conductor 1 in this manner, the coating layer 2 is fixed to the surface of the conductor 1 with high adhesion, impurities such as an oxide film are less likely to form on the surface of the conductor 1, and the contact resistance generated in the conductor 1 can be suppressed.

[0053] It is also preferable that the thickness of the coating layer 2 in the diameter direction of the conductive conductor is a film thickness ratio of 0.1% to 5% of the diameter of the conductive conductor. The conductive conductor on which this film thickness ratio is based can be one with a wire diameter of 1 mm or less. For example, when the thickness of the coating layer 2 is 1 μm for a conductive conductor with a wire diameter of 1 mm, the film thickness ratio is 0.1%. Also, when the thickness of the coating layer 2 is 1.5 μm for a conductive conductor with a wire diameter of 50 μm, the film thickness ratio is 3%.

[0054] If this film thickness ratio is less than 0.1%, it is difficult to obtain a coating layer 2 thick enough to exhibit its function. If this film thickness ratio is more than 5%, the structure becomes similar to that of a copper-clad aluminum (CCA) conductor in which aluminum is the conductive conductor and copper is the coating layer 2, and the coating layer 2 becomes too thick, making it difficult to obtain the weight reduction effect achieved when aluminum is used as the conductive conductor.

[0055] In this way, since the thickness of this coating layer 2 in the diameter direction of the conductive conductor is a film thickness ratio of 0.1% to 5% of the diameter of the conductive conductor, the thickness of this coating layer 2 specified by this film thickness ratio provides more optimal adhesion between the conductor 1 and the coating layer 2, making it less likely for impurities such as an oxide film to form on the surface of the conductor 1, and suppressing the contact resistance generated in the conductor 1.

[0056] The thickness of the coating layer 2 is not particularly limited, but is preferably 0.1 μm to 10 μm, more preferably 0.2 μm to 8 μm, and more preferably 0.3 μm to 6 μm, and can be, for example, 0.5 μm to 2 μm. Since the thickness of the coating layer 2 is 0.1 μm to 10 μm, the specified thickness of the coating layer 2 provides more optimal adhesion between the conductor 1 and the coating layer 2, making it difficult for impurities such as an oxide film to form on the surface of the conductor 1, and suppressing the contact resistance generated in the conductor 1.

[0057] Furthermore, the adhesive strength of the coating layer 2 to the conductor 1 is not particularly limited, but is preferably 6 N or more. Since the adhesive strength of the coating layer 2 to the conductor 1 is 6 N or more, an optimal degree of adhesiveness can be obtained between the conductor 1 and the coating layer 2 due to the adhesive strength of the coating layer 2 to the conductor 1, impurities such as an oxide film are less likely to form on the surface of the conductor 1, and the contact resistance generated in the conductor 1 can be suppressed.

[0058] Furthermore, when the coating layer 2 is made of copper, the Vickers hardness is not particularly limited, but is preferably 100 Hv or more and 200 Hv or less. The indentation hardness corresponding to this Vickers hardness is 1.0 GPa or more and 2.2 GPa or less. The Vickers hardness (or indentation hardness) of the coating layer 2 provides optimal adhesion strength between the conductor 1 and the coating layer 2, making it difficult for impurities such as an oxide film to form on the surface of the conductor 1, and suppressing the contact resistance generated in the conductor 1.

[0059] Furthermore, when the covering layer 2 is made of copper, the indentation modulus (Young's modulus) is not particularly limited, but is preferably 50 GPa to 150 GPa, and more preferably 50 GPa to 140 GPa. This indentation modulus (Young's modulus) provides optimal flexibility between the conductor 1 and the covering layer 2, improving the durability of the conductor 1 against bending operations and providing a cable that can be used for a long period of time with reduced deterioration over time.

[0060] An example of a manufacturing apparatus for manufacturing the above-mentioned conductive conductor will be described below.

[0061] The manufacturing device for manufacturing the conductive conductor according to the present embodiment can be a continuous film forming device equipped with a coating forming means 40 for continuously forming the coating layer 2 on the entire circumference by sputtering, as shown in FIG. 4. The device further includes a source roller 31 for feeding the conductor 1 at one end, a take-up roller 33 for winding up the conductor 1 at the other end, a film forming roller 32 disposed in the vicinity of the coating layer metal plate 20 made of another metal element as a target, a control means 50 for controlling the forward movement of the conductor 1, and an input power 100. The film forming roller 32 is composed of a first film forming roller 32a and another film forming roller 32b, and the control means 50 controls the forward speed C of the conductor 1 and enables the conductor 1 to reciprocate in the vicinity of the coating forming means 40. As shown in FIG. 4, the distance L between the first film forming roller 32a and the other film forming roller 32b (between AB) is set as a film forming region, and the coating forming means 40 forms the coating layer 2 on the conductor 1 by sputtering.

[0062] In this way, since the device is provided with a coating forming means for continuously forming the coating layer 2 around the entire circumference of the conductor 1 by sputtering, the coating layer 2 is evenly and completely coated on the conductor 1, making it difficult for impurities such as an oxide film to form on the surface of the conductor 1 covered with the coating layer 2, thereby suppressing the contact resistance generated in the conductor 1 and significantly improving the durability of the conductive conductor.

[0063] In this embodiment, the conductor 1 is configured to have the coating layer 2 formed thereon, but depending on the purpose and application, a further coating layer may be superimposed on the outside of the coating layer 2 to form a multi-layer structure. For example, depending on the purpose and application, it is also possible to apply tin (Sn) plating to the outermost surface of the coating layer 2 as a further coating layer. With this configuration, when an aluminum alloy is used as the conductor 1 constituting the cable, for example, the highly adhesive coating layer 2 suppresses oxidation of the aluminum surface, and the adhesion of the tin plating can be stably maintained.

[0064] The conductive conductor according to this embodiment has a wide range of applications, and can be used, for example, as cables for industrial robots, cables for use inside aircraft, magnet wires, and the like.

[0065] In order to further clarify the features of the present invention, examples are shown below, but the present invention is not limited to these examples. In the following examples, the names of elements are shown using element symbols for simplicity.

[0066] Example 1 (1) Preparation of conductive conductor (Cu film formation using sputtering) According to the first embodiment, the conductive conductor according to Example 1 was produced by the sputtering apparatus shown in Fig. 1. The inside of the vacuum chamber of the sputtering apparatus was heated to 1000°C by an oil diffusion pump (DP) and a rotary pump (RP). ‐4 After drawing a vacuum to the order of Pa, the chamber was filled with Ar gas to perform film deposition. The pressure was adjusted between 1 and 5 Pa. Cu was used as the target, and DC power was operated in the range of 200 to 600 W. The deposition time was set to 2 to 10 minutes, and the distance d between the Cu target and the Al wire was set to 20 to 80 mm. The short Al-Fe wire in the batch process was fixed with heat-resistant and plasma-resistant tape, and film deposition was performed twice by turning it over. The front and back were turned over by exposing the vacuum chamber to the atmosphere. The film deposition conditions for the Al plate and the short Al-Fe wire are shown in the table below.

[0067] [Table 1]

[0068] The Ni film was formed by changing the target to Ni and the power source to RF. The Ni sputtering film formation conditions are shown in the table below.

[0069] [Table 2]

[0070] (2) Wire evaluation The short Al-Fe wire was evaluated by surface and cross-sectional observation using FE-SEM (Field Emission Scanning Electron Microscopy). The wire cross-section was prepared by fixing the ends of an approximately 10 mm long Al-Fe wire with adhesive and filling it with thermosetting epoxy resin. The end opposite the fixed end was polished with #2000 emery, and then polished with Ar using a CP (Cross-section polisher). + The cross section was made by ion.

[0071] The Ni coating was evaluated using a cross-cut tape peel test. In the cross-cut tape peel test, 1mm x 1mm grid cuts are made, tape is applied, and the state of peeled coating on the sample surface after peeling is observed to qualitatively judge adhesion. If adhesion is high, no peeling is observed in the coating, and if adhesion is low, peeling is observed.

[0072] For the measurement of the film thickness, a flat glass substrate was used, and by masking a portion of the substrate, the height of the film relative to the glass substrate was measured with a contact type roughness meter.

[0073] The electrical resistance was measured using a four-terminal method, measuring the current at the two outer terminals and the voltage at the two inner terminals to evaluate the specific resistance of the coating, excluding the resistance of the measurement system and the contact resistance caused by contact between the terminals and the sample.

[0074] (3) Formation of Cu coating on short Al-Fe wire by sputtering Figure 5 shows an SEM image of the surface of a Cu coating formed on an Al plate in 10 minutes. Figure 6 shows an SEM image of the surface of a Cu coating formed on an Al-Fe wire in 10 minutes. In particular, the 10,000x SEM image confirmed the formation of a finely uneven grain-shaped coating in the Cu coating on the Al-Fe wire.

[0075] Figure 7 shows a cross-sectional SEM image of a Cu-coated Al-Fe wire created with a deposition time of 10 minutes, and cross-sectional SEM images of this Al-Fe wire at 5000x magnification, divided into (A) upper, (B) left, (C) lower, and (D) right parts. From the 5000x SEM images of each part (A) to (D), it was confirmed that the Cu coating was formed almost uniformly on the Al-Fe wire, there was no peeling at the Al-Fe wire / Cu coating interface, and high adhesion was confirmed.

[0076] Figure 8 shows cross-sectional SEM images of the upper (A) and lower (C) parts of Figure 7 at 15,000x magnification. The Cu coating was formed in two layers because it was formed in two batches. The total thickness of the two layers was confirmed to be approximately 1.3 μm.

[0077] Under the deposition conditions used in this study, Cu with a melting point of 1385 K was deposited at room temperature (27°C, 300 K), with a substrate temperature / Cu melting point ratio of 0.22 and deposition pressure of 5 Pa (37.5 mTorr). According to the Thornton model (a microstructural model of thin metal films obtained by magnetron sputtering), which shows the growth model of sputtered films, it is believed that a porous columnar coating was formed, resulting in the formation of a columnar coating with an uneven shape like the collection of fine particles in this study.

[0078] Figure 9(a) shows a cross-sectional SEM image of an Al-Fe wire that was electroplated with Sn on a Cu coating created with a sputtering power of 400 W. The results confirmed that the Cu coating and Sn plating were formed almost uniformly on the circumference of the Al-Fe wire. In addition, the 5000x cross-sectional SEM image on the left in Figure 9(b) confirmed that the Cu coating and the Al-Fe wire were indeed in close contact with each other with an uneven shape.

[0079] Figure 10 shows the elemental mapping of the cross-sectional structure. Because the mass numbers of each element are different, the EDS mapping was recalculated in terms of atomic ratio (at%). Cu and Sn were certainly distributed on the circumference of the Al-Fe wire, just like the other samples.

[0080] Example 2 The surface roughness of each sample of the Al flat plate and the short Al-Fe wire used in the first embodiment was measured using a laser microscope. The samples that were zincated and dried, and those that were zincated and then electroplated with Cu (film thickness 3 μm) were used as comparative examples.

[0081] Fig. 11 shows an image of a surface roughness measurement sample of an aluminum-iron alloy material in which an aluminum plate is coated with copper by sputtering according to Example 2 of the present invention. Also, Fig. 12 shows an image of the surface shape of this surface roughness measurement sample. The results of calculating Ra (arithmetic mean linear roughness) [μm] in the vertical direction from this information, as well as the roughness measurement results other than Ra, are shown in the table below.

[0082] [Table 3]

[0083] It was confirmed that the sputtered Cu coating according to this example had a vertical Ra (arithmetic mean linear roughness) of 0.3 to 0.36 μm, which is larger than the 0.27 μm of the zincate+Cu plating in the comparative example.

[0084] Example 3 According to the first embodiment, an Al plate (100×60×0.5 mm) on which a Cu film was formed by sputtering was polished under running water with Scotch Brite equivalent to #2000 to prepare a sliding base, and measurements were performed using a tensile tester (load cell Max. 10 N) while pulling as vertically as possible. The tensile test was performed at 100 mm / min, which is optimal for a cross-cut tape peel test pulled by hand. If the distance (displacement) at which the tensile test was performed becomes long, instability such as the tape tilting from the vertical occurs, so the adhesion force (N) was measured at a highly stable displacement of 5 to 15 mm. The results of the tensile test are shown in FIG. 13 and the following table.

[0085] [Table 4]

[0086] From the results, it was confirmed that the sputtered film had a high adhesion of 6N or more, and in some cases 7N or more.

[0087] Example 4 For the sample of the Al plate coated with Cu by sputtering in Example 2, the indentation hardness and elastic modulus were measured by nanoindentation using an apparatus (ENT-NEXAS, manufactured by Elionix Corporation). 25 points were measured, and outliers from the median were removed to obtain 10 points of measurement data, from which the indentation hardness (HV equivalent value) and elastic modulus were measured. The indentation depth at the 10 points was 200 nm or less. The conversion formula for the HV equivalent value is HV [kgf / mm 2 ]=92.4 × (indentation hardness [GPa]) Figure 14 shows SEM images of the measurement positions of each sample.

[0088] (1) Measurement results (sample number: Al-210708) The results of the tensile test are shown in Figure 14(a) and in the table below. The average indentation hardness was 1.276 GPa (HV equivalent: 118.09), and the range of indentation hardness was 1.13 to 1.43 GPa (HV equivalent: 104.8 to 132.5). The indentation elastic modulus (Young's modulus) showed a minimum value of 54.95 GPa.

[0089] [Table 5]

[0090] (2) Measurement results (sample number: Al-210729) The results of the tensile test are shown in Figure 14(b) and in the table below. The average indentation hardness was 1.323 GPa (HV equivalent: 122.21), and the range of indentation hardness was 1.16 to 1.52 GPa (HV equivalent: 107 to 140.6).

[0091] [Table 6]

[0092] (3) Measurement results (sample number: Al-210730-2)

[0093] The results of the tensile test are shown in Figure 14(c) and in the table below. The average indentation hardness was 1.698 GPa (HV equivalent: 157), and the range of indentation hardness was 1.33 to 2.04 GPa (HV equivalent: 122.8 to 188.4). The indentation elastic modulus (Young's modulus) showed a maximum value of 139.84 GPa.

[0094] [Table 7]

[0095] Example 5 According to the first embodiment, a Cu sputtered coating was formed on an Al-Fe wire using the sputtering device (continuous film-forming device) shown in Fig. 4 for the conductive conductor according to Example 1. The deposition conditions for the Cu sputtered coating are shown in the following table. The numbers (No.) on the left side of the table indicate the sample numbers of each sample.

[0096] [Table 8]

[0097] Figure 15 shows images of the appearance of the Al-Fe wire before and after the formation of the Cu sputtered coating. It was confirmed that the Cu sputtered coating was continuously formed on the Al-Fe wire of about 2 to 3 m before the coating was formed as shown in Figure 15(a) under all the coating conditions. From the obtained results, as shown in Figure 15(b), it was confirmed that the Cu coating layer was continuously formed by sputtering on the entire circumference of the Al-Fe wire after Cu sputtering.

[0098] (a) Wire evaluation (representative sample number: Al-w231018) The obtained Al-Fe wire was evaluated by surface and cross-sectional observation using FE-SEM (Field Emission Scanning Electron Microscopy). The wire cross-section was prepared by fixing the ends of an approximately 10 mm long Al-Fe wire with adhesive and filling it with thermosetting epoxy resin. The end opposite the fixed end was polished with #2000 emery, and then polished with Ar using a CP (Cross-section polisher). + The cross section was made by ion.

[0099] (b) Cross-sectional SEM observation results Figure 16 shows a cross-sectional SEM image (top) of the Cu-coated Al-Fe wire, and a cross-sectional SEM image (10,000x magnification) of each of the following sections (A) top, (B) left, (C) bottom, and (D) right (bottom). From the 10,000x SEM images of each of the sections (A) to (D), it was confirmed that the Cu coating was formed on the Al-Fe wire to a thickness of about 0.5 to 2 μm, and that because the coating was continuously formed using the sputtering device (continuous coating device) shown in Figure 4, it was formed as a uniform single-layer coating, unlike the coating obtained by batch processing, which has a multi-layered structure. 16, the Cu coating on each of the (A) upper and (C) lower portions was approximately 1 μm thick (1.059 μm and 1.087 μm, respectively), which was confirmed to be approximately the same as the average thickness of the flat Cu film (approximately 1.07 μm) shown on the Al flat plate of sample number Al-210729 in Table 1 of Example 1. It was also confirmed that there was no peeling at the Al-Fe wire rod / Cu coating interface, and that high adhesion was observed.

[0100] Furthermore, as higher magnification cross-sectional SEM images of each of the above (A) to (D), cross-sectional SEM images at 20,000 times are shown in Figure 17. In these cross-sectional SEM images, particularly in the lower part of (C) and the right part of (D), it was confirmed that Cu had penetrated into the uneven shape formed in an anchoring manner on the Al-Fe wire surface (part P in the figure), and thus a Cu sputtered coating had been formed by intrusion. [Explanation of symbols]

[0101] 1 Conductor 2 Covering layer 21 Uneven shape 20 Covering layer metal plate 20a Metal particles 31 Former Roller 32 Film forming roller 32a First film-forming roller 32b Other film-forming rollers 33 Winding roller 40 Covering forming means 50 Control Means 100 Input power 200 Vacuum Chamber 201 Inlet 300 Inert gas ion particles

Claims

1. A conductor made of a metal element or an alloy thereof; a coating layer made of a metal element different from the one metal element or a carbide thereof, coating the conductor and having an uneven shape on a surface on an inner side; The present invention is characterized in that it is composed of Conductor for electrical conduction.

2. The conductor according to claim 1, the one metal element is aluminum, The other metal element is at least one of gold, silver, copper, nickel, tin, titanium, platinum, silicon, cobalt, ruthenium, rhodium, palladium, and indium. Conductor for electrical conduction.

3. The conductor according to claim 2, The other metal element is at least one of gold, silver, copper, nickel, and tin. Conductor for electrical conduction.

4. The conductor according to any one of claims 1 to 3, The uneven shape of the coating layer is formed in an anchoring manner. Conductor for electrical conduction.

5. The conductor according to claim 4, The uneven shape of the coating layer is formed by fitting the conductor surface by sputtering. Conductor for electrical conduction.

6. The conductor according to any one of claims 1 to 3, The coating layer is formed continuously on the surface of the conductor. Conductor for electrical conduction.

7. The conductor according to any one of claims 1 to 3, The thickness of the coating layer in the diameter direction of the conductor for electrical conduction is a film thickness ratio of 0.1% to 5% of the diameter of the conductor for electrical conduction. Conductor for electrical conduction.

8. The conductor according to any one of claims 1 to 3, The thickness of the coating layer is 0.1 μm or more and 10 μm or less. Conductor for electrical conduction.

9. The conductor according to any one of claims 1 to 3, The adhesive strength of the coating layer to the conductor is 6N or more. Conductor for electrical conduction.

10. In the manufacturing apparatus for manufacturing the conductor according to any one of claims 1 to 3, a coating layer forming means for continuously forming the coating layer on the entire circumference of the conductor by sputtering; The present invention is characterized by comprising Manufacturing equipment for conductive conductors.

Citation Information

Patent Citations

  • Conductor for covered wire

    JP1990162608A

  • Conductor for covered wire

    JP1990162611A

  • Method and device for manufacturing superconducting thin film wire

    JP2019183226A

  • Superconducting wire and method for producing the same

    JP2020061235A

  • Plated wire rod material, method for producing same, and cable, electric wire, coil and spring member, each of which is formed using same

    WO2018181399A1